THE RELATIONS BETWEEN OBESITY AND OSTEOARTHRITIS KNEE IN ELDERLY PATIENTS - Arismunandar, Roby (Majority, 2015)
Abstract Background. Obesity is one of the metabolic syndrome, Characterized by the excessive of Body Mass Index (BMI). Obesity can be the beginning of a variety of diseases such as hypertension, coronary heart disease and impotence . The recent studiesdetermining the relationship between obesity and osteoarthritis (OA) of the knee, were found weight gain is often associated significantly as an aggravating factor in OA patients. Discussion. In the knee joint, the adverse effects of excessive weight gain canaccelerate the breakdown of joint cartilage structurefour to five times faster. Osteoarthritis is a musculoskeletal disease that ranks in first position as the cause of pain and disability (inability) in elderly patients that usually attacks the supporting joints, especially the knee joint. Conclusion. This review conclude that patient with obesity have greater risk suffering from knee osteoarthritis disease. The bilateral and unilateral knee OA disease risk increased with age, this due to decreasing of collagen strain and proteoglycans in articular cartilage. Keywords : BMI, elderly,obesity,osteoarthritis. Abstrak Latar Belakang. Obesitas merupakan salah satu metabolic syndrome, yang ditandai dengan Ideks Masa Tubuh (IMT) berlebih. Obesitas dapat menjadi awal dari berbagai penyakit seperti hipertensi, jantung koroner dan impotensi. Berbagai studi menentukan hubungan antara obesitas dan osteoarthritis (OA) lutut, berat badan sering dikaitkan sebagai faktor yang memperparah pasien OA. Pembahasan. Pada sendi lutut, dampak buruk dari berat badan berlebih dapat mencapai empat hingga lima kali lebih besar sehingga mempercepat kerusakan struktur tulang rawan sendi. Osteoartritis merupakan penyakit sendi yang menduduki rangking pertama penyebab nyeri dan disabilitas (ketidakmampuan) pada lansia yang umumnya menyerang sendi–sendi penopang berat badan terutama sendi lutut. Simpulan.Ulasan ini menyimpulkan bahwa obesitas mempunyai faktor risiko Osteoartritis lutut lebih besar, faktor risiko OA lutut bilateral maupun unilateral semakin meningkat dengan bertambahnya umur. Hal ini disebabkan karena adanya hubungan antara umur dengan penurunan kekuatan kolagen dan proteoglikan pada kartilago sendi. Kata kunci: IMT,lansia,obesitas, osteoartritis.